2014
DOI: 10.1186/1556-276x-9-131
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of quadratic electro-optic effects and electro-absorption process in GaN/AlGaN spherical quantum dot

Abstract: Quadratic electro-optic effects (QEOEs) and electro-absorption (EA) process in a GaN/AlGaN spherical quantum dot are theoretically investigated. It is found that the magnitude and resonant position of third-order nonlinear optical susceptibility depend on the nanostructure size and aluminum mole fraction. With increase of the well width and barrier potential, quadratic electro-optic effect and electro-absorption process nonlinear susceptibilities are decreased and blueshifted. The results show that the DC Kerr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Curcumin-loaded PLGA-PEG nanoparticles were 70-300 nm in size and their encapsulation efficiency was 84.5%. It also demonstrated that curcumin has maximum amount of release in a cancer cell-like situation (40°C, pH  5.8) (Kouhi et al 2014, Sadat Tabatabaei Mirakabad et al 2014a, Eatemadi et al 2014, Abbasi et al 2014b, Abbasi et al 2014a, Akbarzadeh et al 2012a.…”
Section: Discussionmentioning
confidence: 96%
“…Curcumin-loaded PLGA-PEG nanoparticles were 70-300 nm in size and their encapsulation efficiency was 84.5%. It also demonstrated that curcumin has maximum amount of release in a cancer cell-like situation (40°C, pH  5.8) (Kouhi et al 2014, Sadat Tabatabaei Mirakabad et al 2014a, Eatemadi et al 2014, Abbasi et al 2014b, Abbasi et al 2014a, Akbarzadeh et al 2012a.…”
Section: Discussionmentioning
confidence: 96%
“…In summary, our results showed that low dosage of β-Cyclodextrin-17AAG complex has more inhibitory effect on expression of hsp90 mRNA than 17AAG free. Besides, β-Cyclodextrin-17AAG complex has fewer side effects than 17AAG free and has more inhibitory effect on hsp90 expression and function; consequently we can use this complex (β-Cyclodextrin-17AAG) as a new anticancer compound in breast cancer treatment (Valizadeh et al, 2012;Mirakabad et al, 2013;Mollazade et al, 2013;Nejati-Koshki et al, 2013;Pourhassan-Moghaddam et al, 2013;Davaran et al, 2014;Kouhi et al, 2014;Wang et al, 2014) …”
Section: Discussionmentioning
confidence: 99%
“…In recent times, a broad range of catalysts for the ring opening polymerization of caprolactone have been reviewed (Alp and Cesur 2013, Bhavsar and Amiji 2008, Fallahzadeh et al 2010 PCL has been standard by the Food and Drug Administration (FDA) in specific applications used in the human body as a drug delivery device, suture or adhesion barrier. A diversity of drugs has been encapsulated within PCL beads for controlled release and targeted drug delivery (Abbasi et al 2014, Jalil et al 2014, Kouhi et al 2014, Yadav 2007.…”
Section: Research Articlementioning
confidence: 99%